Evaluation of Preclinical Class I Amalgam Cavity Preparation: A Comparison of Two Assessment Methods - Haneen Azzuz,; Fatma Soltan,; Asma Abognah, (AlQalam Journal of Medical and Applied Sciences, 2024)
Preclinical assessment forms an effective strategy in undergraduate training. It enhances the continuous development of skills, facilitates early intervention, and optimizes training resources. Constructive feedback provided to the student fosters continuous improvement in preparedness for professional practice and has implications for the development of a learning culture characterized by student activity. This indeed ensures that a smooth transition will be made toward clinical application of skills. The aim of the study was to evaluate examiner`s reliabilities while applying two different assessment methods: a Glance and Grade assessment method and a Checklist and Criteria assessment method. A total of 100 class I amalgam cavity preparations were assessed by three independent examiners to evaluate Class I amalgam cavity preparations on artificial first mandibular molar teeth prepared by second-year undergraduate dental students in a preclinical laboratory setting. Statistical analysis for inter-examiner and intra-examiner variability was tested using one-way ANOVA test and a paired t-test, respectively. Results of this study showed that intra-examiner variability was significantly reduced with Checklist and Criteria assessment method. The inter-examiner variability was present in a Glance and Grade assessment method while with the Checklist and Criteria assessment method, there was an extremely high level of agreement among the examiners. The study's findings indicated considerable variability among examiners using the Glance and Grade assessment method. However, the Checklist and Criteria assessment method demonstrated remarkable consistency among examiners, indicating that it may offer a more standardized and reliable approach to evaluation. يشكل التقييم في المرحلة ما قبل السريرية استراتيجية فعالة في تدريب طلاب المرحلة الجامعية. فهو يعزز التطور المستمر للمهارات ويسهل التدخل المبكر ويعزز من كفاءة استخدام موارد التدريب. كما أن النقد البناء الذي يتلقاه الطالب يساهم في تحسين استعداده المستمر لممارسة المهنة ويؤثر على تطوير ثقافة التعلم للطلاب. وهذا يضمن انتقالاً سلسًا نحو التطبيق السريري للمهارات. هدفت هذه الدراسة إلى تقييم دقة الممتحنين عند تطبيق طريقتين مختلفتين للتقييم: طريقة "النظرة والتقييم" وطريقة "قائمة المراجعة والمعايير". تم تقييم 100 تجويف من الفئة الأولى للأملغم من قبل ثلاثة ممتحنين مستقلين لتقييم تحضير تجويف للأملغم على أسنان صناعية للضرس السفلي الأول, قام بتحضيرها طلاب طب الأسنان في السنة الثانية في المعمل. و قد تم إجراء التحليل الإحصائي لاختبار التباين بين الممتحنين و تقييم كل ممتحن لنفسه باستخدام اختبار (ANOVA) أحادي الاتجاه واختبار( t ) المزدوج على التوالي. أظهرت نتائج هذه الدراسة أن التباين داخل الممتحن نفسه كان منخفضًا بشكل ملحوظ عند استخدام طريقة "قائمة المراجعة والمعايير". و لقد وُجد تباين بين الممتحنين في طريقة "النظرة والتقييم"، بينما كان هناك مستوى عالٍ جدًا من الاتفاق بين الممتحنين عند استخدام طريقة "قائمة المراجعة والمعايير". أشارت نتائج الدراسة إلى وجود تباين كبير بين الممتحنين عند استخدام طريقة "النظرة والتقييم". ومع ذلك أظهرت طريقة "قائمة المراجعة والمعايير" اتفاقًا ملحوظًا بين الممتحنين، مما يشير إلى أنها قد توفر نهجًا أكثر موثوقية وموحدًا للتقييم